القرار المالي وأثره على الأداء المالي مقاس بالربحية-دراسة حالة الشركات الجزائرية - عطاري عبد الناصر; طاري محمد العربي (جامعة الوادي University of Eloued, 2024)
آثار البنية المالية على أداء الشركة العمومية الجزائرية العاملة في قطاع الصناعة والتجارة من منظور نظرية التمويل وهي تقترح على وجه الخصوص، أن اختيار طريقة التمويل، سواء كانت داخَلية أو خارجية، رأس مال خاص، أو ديون طويلة الأجل أو قصيرة الأجل، من المرجح أن تكون له آثار مختلفة على الأداء المالي. ومع ذلك يجب تحديد قياس الأداء ويجب أن تتقارب آثار طرق التمويل هذه بغض النظر عن مؤشر الأداء المختار. ترتبط الديون طويلة الأجل بشكل إيجابي بالأداء المالي للشركة، وترتبط الديون قصيرة الأجل سلبا. وأخيرا، فإن التمويل الذاتي له أيضا تأثير ايجابي على أداء الشركة. The effects of the financial structure on the performance of the Algerian public company operating in the housingsector in the context of the theory of hierarchicalfinancing. Theysuggest in particularthat the choice of a financingmethod, whetherinternal or external, debt or equity, long term or short termislikely to have differenteffects on financial performance. It isstillnecessarythat the performance measurebedefined and that the effects of these modes of financing converge whatever the chosen performance indicator. The longtermdebtispositivelycorrelatedwith the financial performance of the company, the debtruns short. In the end, self-financingalso has a negativeeffect on the company's performance.
Financial decision and its impact on financial performance measured by profitability -a case study of Algerian companies
Keywords: الهيكل المالي; الأداء المالي; طرق التمويل; الشركة العامة; الربحية; Financial Structure; Financial Performance; FinancingMethods; State-OwnedCompany; profitability